"Fair Persuasions"? The Implementation of Laudian Altar Policy in the Diocese of Bath and Wells. Issue 2 (3rd July 2018) - Reeks, John
Abstract : This article investigates the implementation of Archbishop William Laud's restoration of the altars in England in the 1630s, using the Diocese of Bath and Wells, where Laud's ally William Piers served as bishop, as a case study. In so doing, it raises questions about the character of the Laudianism more generally. William Prynne's history of the 1630s continues to influence historiography to the present day, but was constructed to portray Laud and his allies as tyrannical ideologues insensitive to the law, especially regarding the altarwise communion table. Churchwardens' accounts, which allow the Laudian Reformation to be tracked at the parish level, offer an alternative proposition. Here it is argued that Piers, in contrast to certain other 'Laudian' bishops but like Laud himself, was acutely conscious of his precarious legal situation. He adopted a nuanced approach to implementation, moving quickly to enforce the erection of table rails but playing the long game on the altarwise positioning.